Enhancing primary care for older adults: the safety, efficacy, and adherence (SEA) team-based care model to reduce adverse medication outcomes - Michael Changaris; Michael Changaris; Michael Changaris; Michael Changaris; Michael Changaris (Frontiers in Public Health)
IntroductionOlder adults face significant health risks owing to gaps in the management of polypharmacy and medication adherence, as well as the integration of physical and mental health needs. Current models do not fully address these challenges. This study introduced the Safety, Efficacy, and Adherence (SEA) model designed to enhance interdisciplinary collaboration, improve medication management, and integrate care for older adults. This model addresses the core drivers of poor health outcomes: (1) medication adherence challenges, (2) social determinants of health, (3) polypharmacy, (4) team-based care with family support for deprescribing, and (5) psychosocial factors related to aging.MethodsThe SEA model was developed through a structured literature review focusing on medication safety, polypharmacy, behavioral health integration, home safety inspections and adherence. It draws on frameworks such as the Chronic Care Model, Interprofessional Collaborative Care for Older Adults, and Consolidated Framework for Implementation Research. This model fosters interdisciplinary collaboration by integrating pharmacists, primary care providers, mental health professionals, substance use treatment, and family suppowrt, and it is adaptable to diverse clinical settings.ResultsThe SEA model assessed short- and long-term outcomes. Potential short-term effects included improved medication adherence, enhanced team coordination, and reduced occurrence of adverse drug events. Long-term goals and possible effects included better chronic disease management, fewer hospitalizations, and improved quality of life for older adults. The model’s scalability allows for application across various healthcare settings, although further testing is required for validation.ConclusionThe SEA model provides a comprehensive framework for addressing the complex needs of older adults by focusing on medication SEA. Two vignettes, one clinical and one organizational, demonstrate the practical application of the model in patient care and implementation science. By improving interdisciplinary collaboration and addressing social and behavioral factors, in home safety for medications, this model aims to reduce polypharmacy and hospitalization. Based on existing evidence-based frameworks, this model would benefit from future studies to validate its effectiveness in diverse settings.